PERLINDUNGAN HUKUM TERHADAP KORBAN SALAH TANGKAP (STUDI KASUS PENANGKAPAN TERORIS OLEH DETASEMEN KHUSUS 88) - Lena Agustina; Maria Maya Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Performance Detachment 88 combat terrorism lately getting serious attention. Detachment 88 is often indiscriminate action in arresting suspects with terrorism caramelakukan wrongful acts, violent to cause death in which terrorism suspects are still possibilities were not necessarily acts of terrorism. Although terrorism is a form of international crime that is very frightening dimension of the international community and the criminal acts of terrorism can not be justified and inhumane, but the arrest of perpetrators of terrorist acts must also consider that their human rights have been stipulated in the criminal law. The purpose of this thesis research namely; First, the legal protection for victims of wrongful arrests by law in Inodnesia, Second, arrest procedures terrorism cases by Special Detachment 88, Third, weakness Law No. 15 Year 2003 on Eradication of Terrorism.This type of research can be classified in this type of research in which normative legal research this study the authors focus on legal research which examines the legal principles. This study is descriptive, ie a study that aims to create a picture or study in a systematic, timely and accurate based on real facts and to analyze the relationship between the laws and regulations that exist. The purpose of this study found a clear legal basis in putting this issue in the perspective of a special criminal law relating to the protection of victims of wrongful arrests by Detachment 88 in a criminal act of terrorism in Indonesia.From the research, there are three main problems that can be inferred. First, the legal protection for victims of wrongful arrests in Indonesia, namely the presence of the District Court the authority to conduct pretrial, to give; compensation and rehabilitation for someone that case had to be stopped at the second level of investigation, arrest procedures against terrorism suspects in Indonesia consists of: Investigations that can not be separated from the report or complaint, investigation starts from the results of previous investigations where there is preliminary evidence is strong enough, Arrest investigator to the arrest of any person suspected of terrorism is not based on sufficient evidence, detention, for the purpose of investigation is authorized to make arrests. Third, the Policy Act of terrorism must comply with prpsedural mechanism. Advice Author, First, the Act Anti-Terrorism should be immediately amended. Second, the Law Terrorism should consider the principles of sentencing in policy formulation pidanyanya sanctions. Thirdly, It should be in the legislation should also contain strict sanctions for officers of Detachment 88.